The Role of Attention and Memory in EFL Listening Comprehension: A Psycholinguistic Analysis - Cindy Alia Ramadhany; Rosa Anjani; Erna Fitriani Daulay; Yani Lubis (Asosiasi Dosen Muda Indonesia, 2026)
This study investigates the role of attention and memory in EFL listening comprehension from a psycholinguistic perspective. Listening comprehension requires rapid processing of spoken input under time pressure, which places heavy demands on learners’ cognitive resources. This research employed a quantitative correlational design involving undergraduate EFL learners. Data were collected using an attention task, a listening-based working memory task, and a standardized EFL listening comprehension test. Statistical analysis revealed significant positive relationships between attention, working memory, and listening comprehension. The results show that learners with stronger attentional control achieved better listening outcomes, while working memory emerged as the strongest predictor of listening performance. The findings also indicate a close interaction between attention and memory, suggesting that focused attention supports effective memory encoding during listening. These results confirm that listening difficulties are not solely caused by limited linguistic knowledge but also by cognitive constraints. The study contributes to psycholinguistic research by highlighting the importance of general cognitive mechanisms in second language listening. Pedagogically, the findings suggest that EFL listening instruction should consider cognitive load and learners’ processing capacity to support more effective comprehension.